An in silico study of the inhibitory ability of fatty acids and ester derivatives against Streptococcus pneumoniae - Nguyễn Thị, Thanh Hải; Trần, Quang Huy; Nguyễn, Đại Châu; Bùi, Quang Thành; Phạm , Văn Vinh; Nguyễn, Vĩnh Phú; Nguyễn, Công Kính; Phan, Tứ Quý; Nguyễn, Thị Ái Nhung (Hue University Journal of Science: Natural Science, 2026)
Some fatty acids and ester derivatives, namely myristic acid (C1), palmitic acid (C2), pentadecanoic acid (C3), linoleic acid (C4), ethyl palmitate (C5), methyl linoleate (C6) and ethyl linoleate (C7), were studied in silico to inhibit respiratory bacteria (S. pneumoniae). Computational approaches were utilised to evaluate the potential of these compounds against protein Q8DQF8. The positions 1, 2 and 3 are identified as the optimal sites for the docking process, and the docking-based simulation predicts the most effective ligand – Q8DQF8 inhibitory systems in the order: C6 (–11,3 kcal.mol–1) > C3 (–10,9 kcal.mol–1) > C5 (–10,7 kcal.mol–1) > C4 (–9,4 kcal.mol–1) > C2 (–9,0 kcal.mol–1 > C1 (–8,7 kcal.mol–1) > C7 (–8,6 kcal.mol–1). Molecular dynamics simulations for C3, C5 and C6 compounds indicated that C3 exhibits the best interaction with the Q8DQF8 protein. Present results will guide experimental research toward developing new methods to support the treatment of respiratory diseases.